Chemical and spectral data for Lake Towuti drill core - Sheppard, Rachel Y; Milliken, Ralph E; Russell, James M; Sklute, Elizabeth C; Dyar, M Darby; Vogel, Hendrik; Melles, Martin; Bijaksana, Satria; Hasberg, Ascelina; Morlock, Marina A (PANGAEA, 2021)
A thick lacustrine sediment succession in Lake Towuti, located on the island of Sulawesi, Indonesia, offers a unique opportunity to study the relationships between tropical environmental conditions, Fe-rich sediment transport and deposition, and biological and sediment diagenetic processes under variable redox conditions through time. Lake Towuti is located in the East Sulawesi Ophiolite, the third largest ophiolite in the world; several rivers drain into Lake Towuti and supply the lake with high abundances of Fe and other metals from the catchment. The Towuti Drilling Project (TDP) was conducted in 2015 to collect deeper drill-cores from the lake bottom. Over 1000 m of sediment core were recovered, the deepest reaching bedrock at 162.8 m below the lake floor. Major characteristics include basal sediments dominated by silts and sands, overlain by a 2.5 m thick woody peat layer at 100 m depth, reported here as meters composite depth (mcd), and an upper 100 m of alternating thinly bedded red and green clay-sized sediment with localized turbidites, tephras, and diatomaceous oozes. Here we present chemical and spectral data from a 100 m long drill core into lacustrine sediments from a mafic basin. We include the ICP-determined oxide abundances in weight percent of sediment samples and the reflectance spectra of the sediment samples from wavelengths 0.35-28 micrometers.
Keywords: sediment; spectra; tropical lake